High-stakes hedges are misunderstood too. A commentary on: “Valuing bets and hedges: Implications for the construct of risk preference” - Philip W. S. Newall; Dominic Cortis (Judgment and Decision Making, 2019)
Frederick, Levis, Malliaris and Meyer (2018) report a package of laboratory studies where participants underestimate the value of “hedges”: Risky bets which cancel out the risk of another presently-held bet. However, it might be questioned to what extent laboratory findings predict field behavior. People might better understand hedges when more money is at stake, or when they have more time to reflect. We discuss three gamblers who, instead of hedging, used a costly “cash-out” option to eliminate the risk of their bets on Leicester FC’s improbable victory in the 2015/2016 English Premier League soccer season. The decision to cash-out rather than to hedge led to individual losses of up to £8,000, and did not seem plausibly explained by rational economic factors. High-stakes hedges are misunderstood too.